La Noche de la Ciudad Translúcida - Florsheim, Shimrit (Revista de Urbanismo, 2005)
Se presenta la innovación del Hormigón Translúcido, analizando sus posibilidades en arquitectura y urbanismo, además de mostrar sus ventajas en beneficio del ahorro energético y calidad de vida de los habitantes. Abstract The following article presents a creation never seen before: the invention of the translucent concrete. This article analyzes its contribution to Architecture and Urbanism of these days, considering its advantages related with the energy saving and the life quality of the citizens.